EVALUASI KOMPETENSI INDUSTRI 4.0 PADA TENAGA KERJA INDUSTRI DI KABUPATEN KARAWANG - Dimas Syaripudin; Rianita Puspa Sari; Aulia Fashanah Hadining (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Industry 4.0 is called the fourth industrial revolution which brings a paradigm shift in the production industry so that it gives a big impact on the industrial value chain. The concept of industry 4.0 illustrates the increase in digitalization of the entire value chain and results in the interconnection between people, objects and systems through real-time data exchange so that this will be a challenge for companies is facing charges in the era of the industrial revolution 4.0. in this change the company effectively needs to plan for sustainable human resource development. The characteristics of Industry 4.0 that tend to focus on technology and ultimately create a gap between competencies and the expertise needed by Industry 4.0. Therefore, companies need a competency model that is needed by suitable industrial workers in facing industry challenges 4.0. This study aims to analyze the results of the evaluation of employee competencies in companies in the district. Karawang. Employee competency evaluation at companies in the district. Karawang uses multidimensional scaling analysis methods, importance-performance analysis and gap analysis, and radar chart analysis. Based on the results of the study, the multidimensional scaling method aimed at the similarity of characteristics in the use of social competencies and personal competencies of employees in Kab. Karawang has a high similarity of characteristics with the stress value on the perception map of 0.146 or 15% and the R2 value generated is 0.907 or 91%. The largest gap value is owned by the construct of Industry 4.0 competencies with a value of -0.99. The smallest gap value is assumed by the construct of Technical competencies with a value of -0.45. priority levels of competency that need to be improved by employees in Kab. Karawang in the industrial era 4.0 was categorized in the main priorities: social competencies and industry 4.0 competencies, the category of maintaining achievement: Personal competencies and excessive categories: methodological competencies and technical competencies.